Reframing ESP for Educational Technology Students: A Needs Analysis of English Language Demands in Higher Education - Lucia Ekawati Ikanubun; Luciana Calixto (Faculty of Education and Teacher Training of UIN Palopo, 2026)
The development of English courses across various disciplines in higher education has gained increasing attention to address students’ needs. However, few studies have examined the English-language needs of Educational Technology students who serve as instructional designers who must navigate pedagogical discourse and technical documentation in English. The study aims to identify the Educational Technology students’ needs regarding their current abilities, learning difficulties, and perceived needs. The analysis was conducted through three views: Discrepancy, Diagnostic, and Democratic. Data were collected through questionnaires distributed to 93 students and a semi-structured group interview with eight participants. Findings revealed significant gaps in speaking and academic writing, while listening and reading demonstrated moderate proficiency, underscoring the need to strengthen communication skills. Students also demonstrated strong awareness of English's importance to their academic and professional futures, despite considerable gaps in their productive performance. This study contributes to the ESP needs analysis literature in the Educational Technology context, revealing discipline- specific communicative gaps with direct implications for ESP course design. This study furthermore offers concrete guidance for instructors and curriculum developers seeking to design contextualized ESP courses that reflect authentic communicative demands of instructional design practice.